International Joint Ventures and The Value of Growth Options - Tong, Tony W.; Reuer, Jeffrey J.; Peng, Mike W. (Academy of Management Journal, 2008)
According to real options theory, international joint ventures (IJVs) offer valuable growth options, yet there has been no direct evidence of whether, and under what conditions, firms actually capture such value. We argue that an IJV's ownership structure, product-market focus, and geographic location are important contingencies affecting the value of embedded growth options. Our evidence confirms that IJVs do enhance firms' growth option values, but only under certain circumstances. Specifically, minority IJVs and diversifying IJVs contribute to growth option value, but other IJVs do not. The findings also challenge recent claims about the growth option value of investments in emerging economies.